2019
DOI: 10.35631/ijhpl.280011
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Using Jolly Phonics Blending Phonemes to Year 3 English Language Classroom

Abstract: Poor word identifying skill has become an issue among weak students in the education system. Students with good skill of able to identifying words at glance are able to develop and improve their overall reading performance across subjects in the school compared to the weak students who has poor word identifying skill. This problem has not only brought a temporary halt to teachers to teach but also to students to understand any information or tasks transmitted through the teaching and learning process. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Effect sizes ranging from moderate to large were presented in previous empirical studies, signifying the positive effects of multisensory learning on children's PA. In Malaysian settings, findings from this particular study were consistent with previous literature that used Jolly Phonics [20,43,44], OG Approach [24] and self-invented multisensory inspired interventions [8] in enhancing PA among young children in Malaysian rural localities. Findings from this study verified that the intervention did much to ameliorate children's PA.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Effect sizes ranging from moderate to large were presented in previous empirical studies, signifying the positive effects of multisensory learning on children's PA. In Malaysian settings, findings from this particular study were consistent with previous literature that used Jolly Phonics [20,43,44], OG Approach [24] and self-invented multisensory inspired interventions [8] in enhancing PA among young children in Malaysian rural localities. Findings from this study verified that the intervention did much to ameliorate children's PA.…”
Section: Discussionsupporting
confidence: 87%
“…Anthony and Said [43] replicated these findings and found that Jolly Phonics can enhance the PA of primary ESL learners. Ahmad and Yunus [44] also found that this intervention improves the phoneme blending skills of learners. Therefore, Jolly Phonics can improve the PA of young English language learners.…”
Section: Past Studiesmentioning
confidence: 80%
“…To encapsulate, SSP could be the answer for teachers of learners who may be at risk of being left behind and those from a disadvantaged background such as the indigenous groups and/or rural schools (Johnson & Tweedie, 2010) to gain similar improvements in their learners' early literacy in English language. The empirical evidence gathered in the current study also serves to confirm the success of similar projects using systematic phonics for beginning reading (e.g., Hawkins & Su, 2013;Zulkifli & Melor, 2019). However, in addition to reporting the effectiveness of the SSP programme, this article has also thoroughly described the principles and step-by-step procedure of how teachers can carry out the systematic synthetic phonics training in classrooms with their learners.…”
Section: Using Systematic Synthetic Phonics To Accelerate the Acquisition Of Early Literacy Skillssupporting
confidence: 63%
“…A summary of the phases and an overview of the SSP programme are presented in Table 1 and Figure 1, respectively. To date, despite the growing body of literature that supports the benefits of systematic synthetic phonics, little studies have been conducted on children who are English language learners as the majority of those research was focused on native speakers of the English language (McGeown, Johnston & Medford, 2012;Watts & Gardner, 2012;Wyse & Goswami, 2008;Yap, 2014). Therefore, as outlined in the purpose of this article, the next section presents a quantitative randomised comparison experimental study that investigated the effects of SSP and SBELC phonics on reading fluency and spelling ability with a group of indigenous children (Iban) residing in the rural parts of Sarawak.…”
Section: Systematic Synthetic Phonics Programmementioning
confidence: 99%
See 1 more Smart Citation